Query 18

#$&*

course MTH 279

4/5 4:15 pm

Query 18 Differential Equations*********************************************

Question:  A 10 kg mass stretches a spring 30 mm beyond its unloaded position.  The spring is pulled down to a position 70 mm below its unloaded position and released. 

Write and solve the differential equation for its motion.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution: 

gamma = 0

k = (10*9.8)/0.03 = 3270 kg/m

10y'' + 3270y= 0

y''+327y =0

complex roots

±i*18.08

y= A cos 18.08t + B sin 18.08t

y(0) = 0.07

y'(0= 0

A = 0.07

B = 0

y = 0.07 cos 18.08t

confidence rating #$&*:

Good, but the mass is pulled down 70 mm from its unloaded position, which is only 40 mm below its loaded equilibrium position.

@& For comparison:

A 10 kg mass weighs 98 Newtons. Thus a 98 N change in force will change the length of the spring by 30 mm. Assuming the force to be a linear function of the spring we find that the force constant is

k = 98 N / (30 mm) = 3.3 N / mm, approx., or about 3300 N / m.

The new equilibrium position of the system will be 30 mm below the unloaded position. When pulled down 70 mm the position of the system will therefore be -40 mm.

Thus, if y is the position relative to the unloaded position, y(0) = -40 mm and since the spring is released from rest, y ' (0) = 0.

The net force on the system is

F = -k y so that

m y '' = - k y and

y '' = -k/m * y.

The general solution to this equation is

y = A cos(omega t) + B sin(omega t)

with omega = sqrt(k / m) = sqrt(3300 N/m / (10 kg) ) = 18 rad / sec, approx..

We get

y ' = -omega A sin(omega t) + omega B cos(omega t)

The initial conditions give us

y(0) = A = -40 mm

and

y ' (0) = omega B = 0

so that

A = -40 mm, B = 0 and our solution is

y = -40 mm * cos(omega * t).

*@

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution: 

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

 Question:  The graph below represents position vs. clock time for a mass m oscillating on a spring with force constant k.  The position function is y = R cos(omega t - delta).

Find delta, omega and R.

Give the initial conditions on the y and y '.

Determine the mass and the force constant.

Describe how you would achieve these initial conditions, given the appropriate mass and spring in front of you.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution: 

R = 3

y = 3 cos(omega*t - delta)

Two points: (3/4, 0), (5/4, -3)

y(3/4) = 3 cos(3/4omega-delta)= 0

y(5/4) = 3 cos(5/4omega-delta) = -3

cos = 0 at π/2

3/4omega - delta = π/2

cos = -1 at 2π

5/4omega- delta= 2π

@& The cosine is -1 at pi, not 2 pi.*@

omega = 3π

delta = -1.75π

y = 3 cos (3πt +1.75π)

y(0)= 2.121

y'(0)= 20

m = 3 --> omega = 3π --> k= 27π^2

Start mass with 20 cm/s velocity at 2.121 cm

@& Good, but the pi vs. 2 pi creates a discrepancy.

See if you agree with the following:

The period of this function is 2, so omega = 2 pi / 2 = pi.

The amplitude is 3 so the function is of the form y = 3 cos(2 t - delta).

The graph appears to be shifted about 1/4 unit to the right of the graph of y = 3 cos(pi t); replacing t by t - pi/4 will accomplish the shift to the right. Our function is therefore

y = 3 cos( 2 ( t - pi/4) ) ) = 3 cos( 2 t - pi/2).

Thus delta = pi/2, omega = 2 and R = 3.

*@

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution: 

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

*********************************************

Question:  This problem isn't in your text, but is related to the first problem in this set, and to one of the problems that does appear in your text.  Suppose that instead of simply releasing it from its 70 mm position, you deliver a sharp blow to get it moving at downward at 40 cm / second. 

What initial conditions apply to this situation?

Apply the initial conditions to the general solution of the differential equation, and give the resulting function.

 

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution: 

 What changes is y'(0)= 0.4 m/s

y = 0.07cos 18.08t + B sin18.08t

y' = 0.4 = B cos 0

y = 0.07cos 18.08t + 0.4 sin 18.08t

Considering that the loaded equilibrium position is the 40 mm position see if you agree with the following:

Recall that the equilibrium position for the oscillator is 40 mm below its unloaded position.

The 70 mm position is 30 mm below equilibrium, so that initially y = -30 mm, giving us the initial condition

y(0) = -30 mm.

The initial velocity is 40 mm / sec downward, so that

y ' (0) = -40 mm/sec.

As before the equation of motion is

y '' = -k/m * y.

and its general solution is

y(t) = A cos(omega t) + B sin(omega t)

with omega = sqrt(k / m).

y(0) = -30 mm yields A = -30 mm.

y ' (t) = -omega A sin(omega t) + omega B cos(omega t)

so that

y ' (0) = omega * B.

Recall that omega = 18 rad / sec, approx., so

y ' (0) = 18 rad / sec * B = -40 mm / sec

so that

B = -40 mm/s / (18 rad /s) = -2.3 mm.

The equation of motion for the mass is therefore

y(t) = -30 cos( 18 t) - 2.3 sin(18 t).

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution: 

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

*********************************************

Question:  The 32-pound weight at its equilibrium position in a critically-damped spring-and-dashpot system is given a 4 ft / sec downward initial velocity, and attains a maximum displacement of 6 inches from equilibrium.  What are the values of the drag force constant gamma and the spring constant k?

 

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution: 

 y = c1e^(lambda*t) + c2*t*e^(lambda*t)

y(0)= 0 & y'(0)= -4

c1 = 0 & c2 = -4

y = -4te^(lambda*t)

y= -6 --> y'=0

6= -4te^(lambda*t)

0= -4(lambda*t*e^(lambda*t)+e^(lambda*t))

lambda= -1/t

y= -6 @ t= 4.077 --> lambda= 0.245

m= 32/32 = 1 slug

lambda = -gamma/2m --> gamma = -0.49 --> gamma^2 = 4km ---> k = 0.06

y'' -0.49y' + 0.06y = 0

The 6-inch distance would be expressed as 1/2 foot, to make its units consistent with the other units in the problem. This would affect your value of lambda.

Compare with the following, which follows a slightly different (but equivalent) track:

@& If y(t) is the position of the object, the damping force is of form F_damp = - gamma y ' and the spring force is F_spring = - k y so that

F_net = -gamma y ' - k y

and

m y '' + gamma y ' + k y = 0

or

y '' + gamma / m * y ' + k / m * y = 0.

(The unit of mass in the British system is the slug; the weight of 1 slug is 1 slug * 32 ft / s^2 = 32 slug * ft / s^2 = 32 pounds, so our weight has mass 1 slug.

6 inches is 1/2 foot.

y is in units of ft , y ' in units of ft / s^2 and y '' in units of ft / s^2

k * y is in units of lb, so k is in units of lbs / ft, k / m is in units of (lbs / ft) / slugs, which is reduces to s^2

gamma * y ' is in units of pounds, so gamma is in units of lbs / (ft / s) = kg s^-1, so gamma / m is in units of s^-1.

Our conditions are

y(0) = 0

y ' (0) = -4 ft / sec

y(t) = -1/2 ft when | y(t) | is maximized).

The characteristic equation is

r^2 + gamma / m * r + k / m = 0

with solutions

r = (-gamma / m +- sqrt( gamma^2 / m^2 - 4 k / m) ) / 2.

The system is critically damped so the discriminant is 0:

gamma^2 / m^2 - 4 k / m = 0

with the result that

gamma = +-2 sqrt(k * m).

gamma is positive, so we discard the negative solution.

It follows that

r = -gamma / (2 m) = -2 sqrt(k * m) / (2 m) = -sqrt ( k / m )

and our fundamental set is

{e^(-sqrt( k / m) * t, t e^(-sqrt(k / m) * t) }.

Note that we generally use omega is these solutions, where omega = sqrt(k / m). However omega has a strong connotation with angular frequency, and our solutions in the critically damped (and overdamped) cases are not oscillatory so, to avoid possible confusion, we'll leave the notation as sqrt(k / m).

Our general solution is

y(t) = A e^(-sqrt(k / m) * t) + B t e^(-sqrt(k / m) * t).

Initially y = 0 s0

y(0) = 0

giving us

A e^(-sqrt(k / m) * 0) + B * 0 * e^(-sqrt(k / m) * 0) = 0

with the result that

A = 0

giving us

y(t) = B t e^(-sqrt(k / m) * t).

We also note for future reference that

y ' (t) = B e^(-sqrt(k / m) * t) - B t sqrt(k/m) * e^(-sqrt(k / m) * t).

The initial velocity is 4 ft/sec downward so

y ' (0) = - 4 ft / sec

giving us

B e^(-sqrt(k / m) * 0) = -4

so that

B = -4.

Our function is thus

y = -4 t e^(-sqrt(k / m) * t)

and

y ' = -4 e^(-sqrt(k / m) * t) + 4 t sqrt(k/m) * e^(-sqrt(k / m) * t).

(note on units: it should be clear that B is in units of ft / sec; k/m is in units of s^-2 so sqrt(k/m) is in units of s^-1, which is appropriate since t is in units of s)

We are given the weight of the object, and as noted earlier its mass is easily found; in this case the mass is 1 slug.

Our equation is y = -4 t e^(-sqrt(k / m) * t); the only remaining unknown quantity is k.

To evaluate k we use the last bit of given information:

y = -1/2 ft is the position at which distance from equilibrium is maximized.

This occurs when the mass comes to rest, so we have

y(t) = 1/2 when y ' (t) = 0.

y ' (t) = -4 e^(-sqrt(k / m) * t) + 4 sqrt(k / m) t e^(-sqrt(k / m) * t)

y ' (t) = 0 when

y ' = -4 e^(-sqrt(k / m) * t) + 4 t sqrt(k/m) * e^(-sqrt(k / m) * t)

so we solve

-4 e^(-sqrt(k / m) * t) + 4 t sqrt(k/m) * e^(-sqrt(k / m) * t) = 0

for t, obtaining

(4 - 4 t sqrt(k/m) ) e^(-sqrt(k / m) * t) = 0

so that

t = 1 / sqrt(k / m).

So the maximum displacement from equilibrium occurs when t = 1 / (sqrt(k/m)), and at that instant y = -1/2 foot. Writing this as an equation

y(1 / sqrt(k/m)) = -1/2 so

-4 (1 / sqrt(k/m)) e^(-sqrt(k/m) * (1 / (sqrt(k/m) ) ) = -1/2

-4 e^-1 = -1/2 sqrt(k/m)

sqrt(k/m) = 8 / e

(With units the equation -4 e^-1 = -1/2 sqrt(k/m) reads -4 ft / s * e^-1 = -1/2 ft * sqrt(k/m), so that sqrt(k/m) is in units of (ft / s) / ft = s^-1. This is consistent with k in units of lb / ft and mass in slugs (see the earlier note summarizing units)).

k = 8 m / e

(We note that k is therefore in units of mass / time, appropriate units for a force constant).

As seen before gamma = sqrt( 2 k m) so

gamma = sqrt( 2 * (8 m / e) * m ) * m) = 4 m sqrt(1/e).

(the units of k * m are lbs / ft * slugs = kg^2 s^-2, so the units of sqrt(k m) and therefore gamma are kg s^-1, consistent with the units as noted early in the solution).

We calculate our numerical values of k and gamma:

m = 1 (mass is 1 slug) so

k = 8 / e = 2.9 kg / s^2 = 2.9 lb / ft

gamma = 4 m sqrt(1/e) kg s^-1 = 1.45 kg s^-1, or 1.45 lb / (ft / s).

For every foot of stretch the spring exerts 2.9 pounds, and for every ft / sec of velocity the drag force is .30 lb.

Checking against common sense:

The initial drag force is 1.45 lb / (ft / s) * 4 ft /s = 6 lb, approx.. This would result in an initial acceleration of about 6 ft / s^2 on our 1-slug mass.

The maximum spring force is 2.9 lb * 1/2 ft = 1.45 lb.

The time required to reach max displacement is 1 / sqrt(k / m) = .6 second

*@

 Confidence rating: 2.5

.............................................

Given Solution: 

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

*********************************************

Question:  The motion of a system is governed by the equation m y '' + delta y ' + k y = 0, with y(0) = 0 and y ' (0) = v_0.

Give the solutions which correspond to the critically damped, overdamped and underdamped cases.

Show that as gamma approaches 2 sqrt(k / m) from above, the solution to the underdamped case approaches the solution to the critically damped case.

Show that as gamma approaches 2 sqrt(k / m) from below, the solution to the overdamped case approaches the solution to the critically damped case.

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution: 

Overdamped: y= c1e^(lambda1*t) + c2e^(lambda2*t)

y(0)= 0 --> c1 = -c2

y'(0)= v_0 --> c1 = v_0/(lambda1-lambda2)

y = v_0/(lambda1-lambda2)*e^(lambda1*t) - v_0/(lambda1-lambda2)*e^(lambda2*t)

Critically damped: y = c1e^(lambda*t) + c2*t*e^(lambda*t)

y(0)= 0 --> c1 = 0

y'(0)=v_0--> c2 = v_0

y= v_0 e^(lambda*t)

underdamped: y = e^(alpha*t)[c1 cos(beta*t) + c2 sin (beta*t)]

y(0)= 0 --> c1 = 0

y'(0)=0 --> c2 = v_0/beta

y = e^(alpha*t)*(v_0/beta)*sin(beta*t)

I know that omega = sqrt (k/m) when damping is absent and ( sqrt (4km-gamma^2))/2m) when present. As the system becomes more or less damped the second expression moves toward or away from the first.

The cases are based on gamma^2 being <, >, or = to 4km. So I can see how gamma moving toward and away from 4km would approach the other cases but exaclty how this and the above idea relate together is eluding me. If gamma = 2 sqrt (k/m) then gamma^2 = 4k/m and 4k/m < 4km which is always underdamped while m≠1. If this were gamma --> 2 sqrt (km) then it's clear about how the under goes to critical and over goes to critical. As long as gamma> 2 sqrt (km) then it's over and as it goes to 2 sqrt km the damping increases and vice versa. This shows the opposite of what was asked though.

confidence rating #$&*:

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution: 

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary): Not sure about that last part.

This one isn't bad if you consider Taylor series of exponentials, sines, and square roots near 1.

@&

As in the preceding the characteristic equation has solutions

r = (-gamma / m +- sqrt( gamma^2 / m^2 - 4 k / m) ) / 2 = -gamma / (2 m) +- gamma / (2 m) * sqrt( 1 - 4 k m / (gamma^2) ) = -gamma / (2 m) * (1 +-sqrt( 1 - 4 k m / gamma^2) ).

The discriminant is:

zero when gamma = 2 sqrt(k * m),

negative when gamma < 2 sqrt( k * m )and

positive when gamma > 2 sqrt( k * m ) ,

corresponding respectively to the critically damped, overdamped and underdamped cases.

The solution sets are respectively

{e^(-gamma / (2 m) * t), t e^(-gamma / (2 m) * t) }

{e^(-gamma / (2 m) * (1 +sqrt( 1 - 4 k m / gamma^2)) * t), e^(-gamma / (2 m) * (1 -sqrt( 1 - 4 k m / gamma^2)) * t)}

{e^(-gamma / (2 m) * (1 + i sqrt( 4 k m / gamma^2 - 1)) * t), e^(-gamma / (2 m) * (1 - i sqrt( 4 k m / gamma^2 - 1)) * t), which leads to

{e^(-gamma / (2 m) * t) cos(sqrt( 4 k m / gamma^2 - 1)) * t), e^(-gamma / (2 m) * t) sin( sqrt( 4 k m / gamma^2 - 1)) * t)}.

The general solutions can be written as follows (in each case the common factor e^(-gamma / (2 m) * t) has been factored out:

Underdamped case:

e^(-gamma / (2 m) * t) * ( A cos(sqrt( 4 k m / gamma^2 - 1)) * t) + B sin( sqrt( 4 k m / gamma^2 - 1)) * t )

Critically damped case (here we have used C and D as our constants to distinguish them from the constants A and B of the case with which this one is being compared):

e^(-gamma / (2 m) * t) * ( C + D t)

Overdamped case:

e^(-gamma / (2 m) ) * ( A e^(1 +sqrt( 1 - 4 k m / gamma^2)) * t) + B e^((1 -sqrt( 1 - 4 k m / gamma^2)) * t )

Observe that each solution contains the factor e^(-gamma / (2 m) ). We therefore need to show that

as gamma approaches 2 sqrt( k * m ) from above, A cos(sqrt( 4 k m / gamma^2 - 1)) * t) + B sin( sqrt( 4 k m / gamma^2 - 1)) * t approaches the form C + D * t

as gamma approaches 2 sqrt( k * m ) from below, A e^(1 +sqrt( 1 - 4 k m / gamma^2)) * t) + B e^((1 -sqrt( 1 - 4 k m / gamma^2)) * t approaches the form C + D * t

Now, note that

as gamma approaches 2 sqrt( k * m ) from above, the quantity 4 k m / gamma^2 approaches 1 from below so that 1 - 4 k m / gamma^2 approaches zero from above

as gamma approaches 2 sqrt( k * m ) from below, the quantity 4 k m / gamma^2 approaches 1 from above so that 4 k m / gamma^2 - 1 approaches zero from above

We make use of the following facts, easily proven by considering the first two terms of the Taylor series of sin(x), sqrt( x) and e^x:

If epsilon is a small number, then e^(1 +- epsilon) is close to 1 +- epsilon.

If epsilon is a small number, then sin(x) is close to x.

Consider first the overdamped case.

A e^(1 +sqrt( 1 - 4 k m / gamma^2)) * t) + B e^((1 -sqrt( 1 - 4 k m / gamma^2)) * t )

The quantity sqrt( 1 - 4 k m / gamma^2)) * t does approach zero from above, meaning that this quantity approaches zero through positive values.

Letting epsilon = sqrt( 1 - 4 k m / gamma^2)) * t, then our first term is approximately equal to

A * ( 1 + sqrt( 1 - 4 k m / gamma^2)) * t)

and our second term is

B * (1 - sqrt( 1 - 4 k m / gamma^2)) * t )

so that our solution

A e^(1 +sqrt( 1 - 4 k m / gamma^2)) * t) + B e^((1 -sqrt( 1 - 4 k m / gamma^2)) * t )

is approximately equal to

A + B + ( A - B ) sqrt( 1 - 4 k m / gamma^2)) * t

Now let epsilon = sqrt( 1 - 4 k m / gamma^2)). Since sqrt( 1 - epsilon) = 1 - epsilon/2, we have

sqrt(1 - 4 k m / gamma^2) = 1 - 2 k m / gamma^2, approximately. So

A + B + ( A - B ) sqrt( 1 - 4 k m / gamma^2)) * t = (A + B) + (A - B) ( 1 - 2 k m / gamma^2) * t

and as gamma approaches 2 sqrt(k * m) this approaches

A + B + (A - B) * 1/2 * t

which is of the form C + D t for C = A + B, and D = 1/2 ( A - B ).

Consider next the underdamped case.

A cos(sqrt( 4 k m / gamma^2 - 1)) * t) + B sin( sqrt( 4 k m / gamma^2 - 1)) * t.

As gamma approaches 2 sqrt(k m) the term sqrt( 4 k m / gamma^2 - 1)) approaches zero from above, so that

cos(sqrt( 4 k m / gamma^2 - 1))* t) approaches 1

and

sin(sqrt( 4 k m / gamma^2 - 1)) * t) approaches sqrt( 4 k m / gamma^2 - 1)), which in turn approaches 2 k m / gamma^2.

Thus

A cos(sqrt( 4 k m / gamma^2 - 1)) * t) + B sin( sqrt( 4 k m / gamma^2 - 1)) * t

approaches

A + 2 k m / gamma^2 * B * t

which is of the form

C + D t

for

C = A

and

D = 2 k m / gamma^2 * B.

*@

------------------------------------------------

Self-critique rating:

"

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

________________________________________

#$&*

@& You're doing well. Check my notes for a little more on some of these solutions.*@